Fluorimetric and potentiometric study of the conformational transition of isotactic and atactic poly(methacrylic acid) in mixed solvents - Jerman, Boštjan (Acta chimica slovenica, 2006)
Fluorimetric and potentiometric titrations of isotactic (i-PMA) and atactic poly(methacrylic acid) (a-PMA) were performed in methanol-water and in dioxane-water mixtures with varying contents of organic solvent. Fluorimetric investigation of a-PMA confirmed previous reports that the conformational transition of the atactic chain disappears when organic solvent content exceeds 40 and 20 % of methanol and dioxane, respectively. For the i-PMA chain, potentiometric data revealed that the conformational transition occurs in methanol-water mixtures with up to 60 % of methanol in approximately the same region of degree of neutralization (áN) as in water. Besides, the irreversibility of this transition does not disappear. On the other hand, the discontinuity in the potentiometric titration curve in dioxane-water mixtures is no longer detectable in 50% dioxane. Concurrently, i-PMA dissolves in 50% dioxane at N = 0, whereas it is not soluble in unneutralized state in any of the pure solvents. The observed behavior is attributed to high tendency of dioxane for hydrogen bond-formation both with water and with PMA. The nature of the change in chain dimensions upon neutralization for i-PMA in 50% dioxane is discussed. Results are discussed also in view of a high intermolecular association tendency of PMA chains.
Keywords: fizikalna kemija; fluorimetrične titracije; polielektroliti; polimetakrilna kislina; potenciometrične titracije; površinsko aktivne snovi; raztopine